Use of ultrasound-activated resorbable sheets and pins in the management of fractures of the condylar neck of the mandible: a case series. Issue 3 (April 2018) - McLeod, N.M.H.; Van Gijn, D.
Abstract: The need to treat fractures of the mandibular condyle remains controversial, but when the decision to operate has been made, then multiple forms of fixation are advocated. Traditionally, metal plates and screws have been used, but this is thought to have several disadvantages, particularly in the growing skeleton. Resorbable fixation for maxillofacial fractures has not gained widespread acceptance because of technical difficulties with the materials and concern about inflammatory reactions during their resorption. Because not all patients have typical fracture patterns that fit the size and shape of metal plates, mouldable resorbable fixation materials can be useful, and ultrasound-activated resorbable sheets and pins have the necessary stability to fix fractures of the condylar neck. We present a series of patients in whom ultrasound-activated resorbable sheets and pins were used to fix condylar fractures in which the fracture pattern did not permit the use of stable metal fixation, or the age of the patient in our opinion precluded the use of metal fixation. There were no perioperative complications and no problems related to the stability of the fixation. Minor swelling relating to the resorption of the material in one case did not require any management.